PENDIDIKAN KAUM SUFI DI INDONESIA (Materi dan Metode Pendidikannya) - Suheri Sahputra Rangkuti (Universitas Muhammadiyah Metro, 2018)
Sufis are part of the nomenclature of Islam in Indonesia. its existence which is already old even almost simultaneously with the entry of Islam into Indonesia certainly has involvement and contribution in building the nation. In addition, the pattern of tarekat in Indonesia which does not negate the worldly orientation is able to encourage change. Therefore, this article wants to reveal the material and methods of education to contribute ideas to enrich the treasures of Islamic education.